Project Based Learning Model to Improve Communication Skills and Science Learning Outcomes - Hasanah, Alif Nur; Purwandari, Purwandari; Marsiti, Marsiti (Science Education and Application Journal, 2023)
21st century learning does not only focus on learning outcomes but also emphasizes the 4C skills. One of the 4C skills that must be mastered by students is communication skills. Communication skills can be trained and developed through the application of a project-based learning model ( PjBL). PjBL is one of the learning models which is the main program of choice in an independent curriculum that can bridge the development of student’s communication skills. Good communication skills affect mastery of the material and student learning outcomes. The purpose of this study was to determine the effect of the project based learning model in improving communication skills and science learning outcomes. This type of research is classroom action research which consists of two cycles. Each cycle includes planning, implementation, observation, and reflection. The results of the first cycle of reflection were analyzed, then in revision to improve learning in cycle II. The research design uses the Kemmis and Mc. Taggart. The results showed that student’s communication skills increased from 60% (enough) in Cycle I to 75% (good) in Cycle II. In addition, the mastery of student learning outcomes also increased from Cycle I by 60% to 84% in Cycle II. Thus, it can be concluded that communication skills and science learning outcomes for class VII-E students of SMPN 6 Madiun can be improved by applying a project-based learning model.